2021
DOI: 10.4103/jpbs.jpbs_634_20
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Photogrammetric Landmarks to the Conventional Cephalogram for Analyzing Soft-Tissue Landmarks in Orthodontics

Abstract: Background: Graber introduced facial photographs as an internal diagnostic aid. Facial photographs could serve as an important alternative assessment tool in the absence of equipment for cephalometric analysis. Objectives: The present study was aimed at assessing whether analyzing the photographs could have precision for assessing the landmarks appropriate for facial analysis. In addition, the relationship between frontal cephalogram and measurements on photographs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As an alternative, MRI scans can be used in some patients (e.g., with craniofacial disorders); however, these remain inferior for orthodontic cephalometric analysis [21]. In a similar manner, digital photography alone can be used, to some extent, for landmark identification and facial analysis to alleviate the need of more invasive investigations [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, MRI scans can be used in some patients (e.g., with craniofacial disorders); however, these remain inferior for orthodontic cephalometric analysis [21]. In a similar manner, digital photography alone can be used, to some extent, for landmark identification and facial analysis to alleviate the need of more invasive investigations [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies utilizing posteroanterior radiographs have reported increases in nasal, maxillary and zygomatic width following RME, reflecting changes in hard tissues [18,20,21]. However, the impact of these alterations in hard tissues on the soft tissues has not been thoroughly investigated [18,[22][23][24]. Recent orthodontic treatment plans have placed a greater emphasis on enhancing soft tissues rather than solely focusing on tooth alignment, with the primary goal of improving facial esthetics [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the cost of 3D imaging devices makes them inaccessible in many orthodontic clinics. Alternatively, orthodontic clinics routinely obtain photographs and radiographs from patients at the beginning, mid-stage and completion of treatment, allowing for clear observation of not only the changes in dentition and skeletal structure but also alterations in soft tissues resulting from orthodontic interventions [23,24].…”
Section: Introductionmentioning
confidence: 99%